استعمال أدوات محاسبة التكاليف كآلية لرفع و زيادة قدرة المؤسسة التنافسية /دراسة حالة بالمؤسسة الوطنية للدهن وحدة سوق اهراس - محمد الهادي قياس; محمد حزايمية (My University, 2021)
Involve the swift evolution occurring in business environment, the economic institution needs to adapt to external changes, and it should keep pace with the economic events that occur. Also, it needs to monitor its competitors, that’s what require the institution to develop strategies for raising competitiveness, and finding ways to preserve its position on the market for as long as possible. In order to get these goals, the institution needs to think about the optimum use of the cost accounting tools, that promotes to the optimal use of the available productive resources, besides it encourages the efforts to be directed towards the growth of the company, and increasing its competitiveness. In this research, the main objective was the impact of the use of cost accounting tools on increasing the competitiveness of the ENAP company, Souk Ahras Unit. The data obtained was analyzed and interpreted using statistical analysis methods, and the results of the study were reached. ........................................... تنطوي على التطور السريع الذي يحدث في بيئة الأعمال، وتحتاج المؤسسة الاقتصادية إلى التكيف مع المتغيرات الخارجية، وعليها أن تواكب الأحداث الاقتصادية التي تحدث. كما أنها تحتاج إلى مراقبة منافسيها، وهذا ما يتطلب من المؤسسة وضع استراتيجيات لرفع قدرتها التنافسية، وإيجاد السبل للحفاظ على مكانتها في السوق لأطول فترة ممكنة. ولتحقيق هذه الأهداف تحتاج المؤسسة إلى التفكير في الاستخدام الأمثل لأدوات محاسبة التكاليف، التي تعزز الاستخدام الأمثل للموارد الإنتاجية المتاحة، كما تشجع الجهود لتوجيهها نحو نمو الشركة، و زيادة قدرتها التنافسية. في هذا البحث كان الهدف الرئيسي هو أثر استخدام أدوات محاسبة التكاليف على زيادة القدرة التنافسية لشركة ENAP وحدة سوق أهراس. وتم تحليل البيانات التي تم الحصول عليها وتفسيرها باستخدام أساليب التحليل الإحصائي، وتم التوصل إلى نتائج الدراسة.